ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Wahyudi, Amin - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2006)
ABSTRACT Target of this research is to know leadership style, environment work and motivation that influence and significantly to officer performance in Office Information Communications and Public relations Sub-Province Boyolali by partial and together and also to know among leadership style, environment and motivation, what most dominant variable have an effect to performance. In data collecting conducted by and observation divide of questioner to be filled to responder counted 51 officers. From the regression known that variables of leadership style, motivation and environment work have a positive and significant effect to officer performance by partial and also together and among leadership style, motivation and environment work, that most dominant have an effect to performance is environmental work variable. Independent variable (leadership style, motivation and environment work) contribution can explain its influence to dependent variable (performance) equal to 78,8%, while the rest 21,2% influenced by other variables which not checked (outside research variables). Result of assumption classical test known that there is no deviation to classic assumption. Keywords: leadership style, motivation, environmental work, performance.